Measurement of extremely 2H‐enriched water samples by laser spectrometry: application to batch electrolytic concentration of environmental tritium samples. (5th January 2016) - Wassenaar, L. I.; Kumar, B.; Douence, C.; Belachew, D. L.; Aggarwal, P. K.
Abstract : Rationale: Natural water samples artificially or experimentally enriched in deuterium ( 2 H) at concentrations up to 10, 000 ppm are required for various medical, environmental and hydrological tracer applications, but are difficult to measure using conventional stable isotope ratio mass spectrometry. Methods: Here we demonstrate that off‐axis integrated cavity output (OA‐ICOS) laser spectrometry, along with 2 H‐enriched laboratory calibration standards and appropriate analysis templates, allows for low‐cost, fast, and accurate determinations of water samples having δ 2 HVSMOW‐SLAP values up to at least 57, 000 ‰ (~9000 ppm) at a processing rate of 60 samples per day. Results: As one practical application, extremely 2 H‐enriched samples were measured by laser spectrometry and compared to the traditional 3 H Spike‐Proxy method in order to determine tritium enrichment factors in the batch electrolysis of environmental waters. Highly 2 H‐enriched samples were taken from different sets of electrolytically concentrated standards and low‐level (<10 TU) IAEA inter‐comparison tritium samples, and all cases returned accurate and precise initial low‐level 3 H results. Conclusions: The ability to quickly and accurately measure extremely 2 H‐enriched waters by laser spectrometry will facilitate the use of deuterium as a tracer in numerous environmental and other applications. For low‐level tritium operations, this new analytical ability facilitated a 10–20 % increase in sample productivity through the elimination of spike standards and gravimetrics, and provides immediate feedback on electrolytic enrichment cell performance. Copyright © 2016 John Wiley & Sons, Ltd.